DESIGN AND CONTROL OF MECHANICAL STRUCTURE OF LEGO ROBOT WITH 3 DOF - Gheorghe GÎLCĂ; BÎZDOACĂ Nicu - George (Fiabilitate şi Durabilitate)
This paper discusses a simplified design of Humanoid Robot with 3 DOF. The main objective is to analyze the theoretical and practical challenges involved in making it. The paper emphasis bringing down the control complexity by reducing the number of actuators used, three, one for each degree of freedom. . This in turn simplifies the entire design processes and reduces the production cost. It also describes the stability issues and different walking phases in detail. The proposed robot can be placed between simple, miniaturized humanoids and the most advanced, sophisticated humanoids. The humanoid robot is programmed to go forward, backward, to rotate, to stop when it encounters obstacles. He uses two sensors: one touch, which works as a command button and one ultrasonic which determines the distance to objects.